Aplikasi Jamur Antagonis Trichoderma viride Terhadap Pengurangan Intensitas Serangan Penyakit Hawar Daun Serta Hasil Tanaman Kentang - Purwantisari, Susiana (Prosiding KPSDA, 2015)
The  objective  of  this  research was  to  studi  ability  of Trichoderma sp. fungal antagonist on reduction leaf blight intensity disease and potato yield. The in vivo experiment was carried  out  at  potato  land  area  located  at  BALITSA in Cikole Sub District, Lembang  District and Bandung Regency. Completely  Randomized  Design  was  used  with  six treatment and five replicates. The treatment tested consist of control  (without pathogen fungal and antagonists fungus application too), control (with  pathogen fungal application and without antagonist fungal application), chemical fungicide application, antagonist fungal application 2 weeks before planting, application 1 week after planting and both application 2 weeks before and 1 week after planting. Result of  the  research  showed  that  application of antagonists fungal could decrease disease intensity and tended to improve crop potato yield. Research repeatment with more quantity pouring the antagonist was needed. These antagonist could be used as biological agents initials to control leaf blight disease.